Assessment of Sustainable Intensification Practices in Babati District - World Vegetable Center (International Food Policy Research Institute, 2019)
The survey aimed at collecting data on five sustainable intensification domains which the Africa RISING project was established to assess the contribution of the project in improving vegetable farming practices. The domains are: productivity, economic, environment, social and human condition. This survey covered the vegetable theme/components and the data was collected from among vegetable growing households. Around 310 farmers were interviewed, the sample in each village constitute over 50% of the total vegetable growing population.